Extraction, separation and refining of microcrystalline cellulose from wheat straw using various pretreatments - Jinbao, Li; Huiling, Dong; Huijuan, Xiu; Meiyun, Zhang; Reddy, Kamireddy Srinivas; Xuefei, Zhang; Yun, Ji (International Journal of Agricultural and Biological Engineering, 2016)
This study focused on the manufacture of microcrystalline cellulose (MCC) from wheat straw using environmentally-friendly solvents. Raw cellulose was separated from wheat straw after thermal decomposition of lignin followed by dissolution of lignin using a recyclable ethanol/acetic acid/water solvent system. Then, pure cellulose was produced using a four-step refining process, including chelating, O3, H2O2, and xylanase treatments. Finally, MCC was obtained through hydrolysis, drying, and mechanical treatments. The effects of acetic acid, O3, H2O2, NaOH, pretreatment time, and temperature on the properties of wheat straw cellulose (including Kappa number, yield, α-cellulose content, crystallinity, KMnO4 value, degree of polymerization (DP), and brightness) were investigated. The results showed that the addition of acetic acid enhanced lignin removal and hemicellulose degradation, improving the purity of the raw cellulose. The optimized acetic acid dosage in the wheat straw thermal decomposition step was 2% (w/w). The optimized O3 dosage was 1.2% (w/w). The optimized conditions for H2O2 treatment were found to be 3% (w/w) H2O2 and 1.8% (w/w) NaOH at 70°C for 120 min. The KMnO4 value was 2.0, brightness was 84.1% ISO, the viscosity was 934 mL/g, and the DP was 626 for refined cellulose. Xylanase effectively improved the α-cellulose content of wheat straw cellulose. With an optimized xylanase dosage of 1.5 IU/g, the α-cellulose content was 94.7%, the brightness was 85.6% ISO, and the DP was 615 for wheat straw cellulose. Keywords: wheat straw, cellulose; separation, refining, low pollution process, microcrystalline cellulose (MCC) DOI: 10.3965/j.ijabe.20160902.1386 Citation: Li J B, Dong H L, Xiu H J, Zhang M Y, Reddy K S, Zhang X F, et al. Extraction, separation and refining of microcrystalline cellulose from wheat straw using various pretreatments. Int J Agric & Biol Eng, 2016; 9(2): 137－145.